2010
DOI: 10.1111/j.1365-277x.2009.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional vitamin A status in northeast Brazilian lactating mothers

Abstract: On the basis of the intake of the pro-vitamin A carotenoids, some women may be at risk of vitamin A deficiency. However, their status is currently normal, as indicated by serum and milk retinol concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 28 publications
1
39
0
3
Order By: Relevance
“…The mean colostrum retinol concentration observed here was in line with what has been observed with breastfeeding mothers in industrialized nations (50 to 70μg/dL) and superior to the mean among women in non-industrialized countries (40μg/dL) (29) . The figures for serum retinol observed in this study are in line with figures observed in Spain (14) and Bangladesh (30) and in populations similar to the population studied here (31) and are higher than figures for breastfeeding mothers in Africa (32) .…”
Section: Discussionsupporting
confidence: 91%
“…The mean colostrum retinol concentration observed here was in line with what has been observed with breastfeeding mothers in industrialized nations (50 to 70μg/dL) and superior to the mean among women in non-industrialized countries (40μg/dL) (29) . The figures for serum retinol observed in this study are in line with figures observed in Spain (14) and Bangladesh (30) and in populations similar to the population studied here (31) and are higher than figures for breastfeeding mothers in Africa (32) .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Ribeiro et al [25] and Schulz et al [39] did not find linear correlations between maternal diet and the retinol and betacarotene levels. The highly positive association between retinol levels and colostrum betacarotene corroborates the findings of Canfield et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of low VA levels in children under 5 years was found in the Northeast (19.0%) and Southeast (21.6%) regions of the country, although there were no statistical differences between macroregions when evaluating women . In the Brazilian Northeast context, many studies have reported a high probability of this kind of deficiency occurring among women attending public hospitals in this region, which suggests that DVA can result in serious prejudice for the health of women and their babies in the intiial days after childbirth. Faced with these circumstances, it is important that studies assess the VA status of populations at risk of developing VAD, such as those in the Brazilian Northeast.…”
Section: Introductionmentioning
confidence: 99%